Design and Development of a Water Flow Monitoring Device using Mitsubishi FX3U-14MT PLC - Herri Trisna Frianto; Syahrul Humaidi; Kerista Tarigan; Dadan Ramdan; Doli Bonardo; Fauzan Amri (Journal of Engineering and Technological Sciences, 2026)
Efficient water management is essential for ensuring sustainability and reducing operational costs, especially in small to medium-scale buildings such as schools, health clinics, and office facilities. This paper presents the design and implementation of a cost-effective automated water flow monitoring system, integrating a Mitsubishi FX3U-14MT PLC with an Arduino module to facilitate real-time flow measurement and precise control of solenoid valves. The PLC is programmed using ladder logic, while the Arduino is responsible for processing sensor data, thereby enhancing measurement accuracy and contributing to overall system flexibility. In contrast to conventional industrial automation solutions, this system is specifically designed for small-scale applications, offering an effective balance of affordability, simplicity, and reliability. Experimental testing demonstrates that the system achieves high measurement accuracy, operational stability over extended use, and optimized energy efficiency, ensuring long-term reliability in water flow management. Additionally, the system’s modular design enables straightforward adaptation to various facility sizes and plumbing configurations. These findings validate the proposed system as an accessible yet effective automation solution, particularly suitable for environments where implementing large-scale industrial control systems may be impractical. Future research could focus on incorporating adaptive control algorithms and enhancing sensor integration to further improve system performance and flexibility.